Are Statutory Requirements Followed in the Certification of Traumatic, Unexpected, and Unattended Deaths in Missouri?. Issue 6 (30th March 2018) - Xaverius, Pamela K.; Wambuguh, Loise; Ward, Craig; Salas, Joanne; Alleman, Elizabeth; Young, Jeffrey; Berkemeier, Jessica
Abstract: Medical examiners and coroners (ME/Cs) investigate deaths important to public health. This cross‐sectional study evaluated 343, 412 death certificates from 2007 to 2012 in Missouri. We examined agreement between cause and manner of death by year and ME/C contact as well as 2010–2012 trends in ME/C contact. There was near perfect agreement between cause and manner of death when an ME/C was contacted (kappa=0.97, p < 0.0001) and a significant increase in the proportion of deaths with ME/C contact from 2010 to 2012 ( p =< 0.0001). There was a significantly higher proportion of ME/C‐certified deaths using the electronic system in 2010–2012 (aOR = 1.18, 95% CI 1.15, 1.21) compared to the manual system in 2007‐2009. Black, non‐Hispanic (aOR = 1.50, 95% CI 1.43, 1.57) and Hispanic (aOR = 1.31, 95% CI 1.13, 1.51) deaths, compared to White, non‐Hispanic deaths, were associated with a significantly greater odds of ME/C certification. Race as an independent predictor of ME/C death certification warrants further research.